Diversity and Proliferation of Metallo-β-Lactamases: a Clarion Call for Clinically Effective Metallo-β-Lactamase Inhibitors - Somboro, Anou M. (Appl Environ Microbiol, 2018)
The worldwide proliferation of life-threatening metallo-β-lactamase (MBL)-producing Gram-negative bacteria is a serious concern to public health. MBLs are compromising the therapeutic efficacies of β-lactams, particularly carbapenems, which are last-resort antibiotics indicated for various multidrug-resistant bacterial infections. Inhibition of enzymes mediating antibiotic resistance in bacteria is one of the major promising means for overcoming bacterial resistance. Compounds having potential MBL-inhibitory activity have been reported, but none are currently under clinical trials. The need for developing safe and efficient MBL inhibitors (MBLIs) is obvious, particularly with the continuous spread of MBLs worldwide. In this review, the emergence and escalation of MBLs in Gram-negative bacteria are discussed. The relationships between different class B β-lactamases identified up to 2017 are represented by a phylogenetic tree and summarized. In addition, approved and/or clinical-phase serine β-lactamase inhibitors are recapitulated to reflect the successful advances made in developing class A β-lactamase inhibitors. Reported MBLIs, their inhibitory properties, and their purported modes of inhibition are delineated. Insights into structural variations of MBLs and the challenges involved in developing potent MBLIs are also elucidated and discussed. Currently, natural products and MBL-resistant β-lactam analogues are the most promising agents that can become clinically efficient MBLIs. A deeper comprehension of the mechanisms of action and activity spectra of the various MBLs and their inhibitors will serve as a bedrock for further investigations that can result in clinically useful MBLIs to curb this global menace.